Fabrication and mechanical properties of composite palm ash mixed with phenolic resins - Mohd Radzi, Ali; Shamsul Baharin, Jamaludin, Prof. Dr.; Nur Hidayah, Ahmad Zaidi; Che Mohd Ruzaidi, Ghazali, Prof. Madya (International Network for Scientific Information Publication (INSI), 2012)
Link to publisher's homepage at http://www.insipub.com/